PENEGAKAN HUKUM OLEH KEPOLISIAN DALAM TINDAK PIDANA PENCURIAN DENGAN KEKERASAN DI KEPOLISIAN RESOR INDRAGIRI HILIR - Zulham Daris Firidho; Erdianto Effendi; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Theft with violence in Indragiri Hilir often happens because of the population growth is increasingly growing, so as to create conditions of population growth affect the socio-economic conditions of society, especially relating the fulfillment of the necessities of life and employment field. Theft with violence occurred in 2013 and 2015 amounted to 67 cases successfully handled by Police Indragiri Hilir, the number was certainly very much and very harm the victim.This type of research is classified as socio-juridical research, because this research author directly conduct research on the location or point examined in order to provide a complete and clear picture of the issues examined. This research was conducted at the Police Indragiri Hilir, while the sample population is a whole party with regard to the issues examined in this study, the data source used, primary data, secondary data, and the data tertiary, data collection techniques in this study carried out by interviews, questionnaires, and literature study.The research problems are, among others: first, What factors encourage the offender committed the crime of theft with violence in the Police Resort Indragiri Hilir, second, What forms of preventive efforts undertaken by the investigator Police Resort Indragiri Hilir the criminal case of theft with violence, third , What efforts should be made by the investigator to conduct repressive efforts against the criminal cases of theft with violence in Indragiri Hilir. Results of the study are: first, the cause of the crime of theft with violence actually originated from the education factor, everything in an instant though in a way that is not true of society whose economy is down to the middle tend to commit the crime of theft with violence, the second, preventive efforts Police Indragiri downstream of the criminal case of theft with violence, among others; Conducting Kring Serse in order mastery region, narrowing the motion offenders in particular theft with violence, early detection of the perpetrators of crimes of theft with violence by gathering as much information crimes including theft with violence and syndicate groups, third, repressive efforts against cases of crime of theft with violence in Indragiri Hilir to take action against the perpetrators in accordance with the deeds and fix it back so that they are aware that the act of doing was a violation of law and detrimental to the public, so as not to repeat it and others will not do so given the sanctions that bear a very heavy.Keywords: Law Enforcement - Crime - Curas